2000
DOI: 10.21273/hortsci.35.6.1022
|View full text |Cite
|
Sign up to set email alerts
|

The Composition of Strawberry Aroma Is Influenced by Cultivar, Maturity, and Storage

Abstract: Strawberry (Fragaria ×ananassa Duch.) fruit have a unique, highly desirable flavor and are one of the most popular summer fruits. Sugars, acids, and aroma volatiles contribute to the characteristic strawberry flavor, which is dependent on the proper balance of these chemical constituents. While sugars and acids are responsible for the sweetness and tartness of the fruit, aroma volatiles provide the unique, fruity flavors that characterize a fresh strawberry. The aroma of fresh strawberries is dependent on many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
129
1
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(141 citation statements)
references
References 22 publications
7
129
1
4
Order By: Relevance
“…Thus, the more-volatile analytes might be more easily extracted, and appear at comparatively higher concentrations. This reflects the compound's contribution to the fruit aroma, but does not give its true concentration in the tissue [7]. Ultimately this method of extraction could not be used to accurately quantify the level of compounds in the sample, a problem other authors have encountered with this sampling approach [32,15].…”
Section: Whole Fruit Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the more-volatile analytes might be more easily extracted, and appear at comparatively higher concentrations. This reflects the compound's contribution to the fruit aroma, but does not give its true concentration in the tissue [7]. Ultimately this method of extraction could not be used to accurately quantify the level of compounds in the sample, a problem other authors have encountered with this sampling approach [32,15].…”
Section: Whole Fruit Analysismentioning
confidence: 99%
“…Strawberries have a complex aroma with more than 360 identified constituents composed of alcohols, esters, aldehydes, ketones and furanones [5]. This complexity is compounded by the fact that aroma is known to vary with berry variety [6,7], season, and agronomic and climatic growing conditions [8]. Furthermore, Watson et al [9], have shown that volatiles examined in the variety Elsanta, showed highly significant differences with harvest date (pick-to-pick variation; P < 0.01) and even between fruit on a single harvest date.…”
Section: Introductionmentioning
confidence: 99%
“…Even though these volatiles comprise about 0.01 to 0.001% of the fresh fruit weight, they have a significant impact on the overall flavor of strawberry (Buttery 1981). Strawberry aroma is dependent on many factors, and studies report that genotypes or cultivar exhibit considerable variations in the profiles of the volatiles they produce (Forney et al 2000). In this study, cultivars exhibited distinct differences in the chemical composition of volatiles.…”
Section: Discussionmentioning
confidence: 70%
“…Recently, caryophyllene oxide has shown cytoxicity against several cancer cell lines (Jun et al 2011). Previous studies reported that esters comprised 25Á90% of the total number of volatiles in ripe strawberry fruit (Perez et al 1992;Forney et al 2000). Among the esters, butanoates comprised the predominant proportion of esters.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation